Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1023/a:1021997924473
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Voltage-gated calcium channels (VDCC) are essential to neuronal maturation and differentiation. It is believed that important signaling information is encoded by VDCC-mediated calcium influx that has both spatial and temporal components. VDCC are multimeric complexes comprised of a pore-forming alpha1 subunit and auxiliary beta and alpha2/delta subunits. Changes in the fractional contribution of distinct calcium conductances to the total calcium current have been noted in developing and differentiating neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…51, 121, 420, 460, 461, 474). Nevertheless, in lethargic mice, there is increased pairing of Ca v 2.2 and Ca v 2.1 with other Ca v βs; in particular, both β 1b and Ca v 2.2/β 1b complexes are upregulated, similar to what is found in the developing brain (310, 311). Some other characteristics of lethargic mice include lower N-type channel expression in the forebrain and cerebellum (310), reduced excitatory neurotransmission in the thalamus (57), a modified electro-oculogram (301), splenic and thymic involution (130, 131), and renal cysts (130).…”
Section: Cavβ Knockouts and Pathophysiologysupporting
confidence: 55%
See 2 more Smart Citations
“…51, 121, 420, 460, 461, 474). Nevertheless, in lethargic mice, there is increased pairing of Ca v 2.2 and Ca v 2.1 with other Ca v βs; in particular, both β 1b and Ca v 2.2/β 1b complexes are upregulated, similar to what is found in the developing brain (310, 311). Some other characteristics of lethargic mice include lower N-type channel expression in the forebrain and cerebellum (310), reduced excitatory neurotransmission in the thalamus (57), a modified electro-oculogram (301), splenic and thymic involution (130, 131), and renal cysts (130).…”
Section: Cavβ Knockouts and Pathophysiologysupporting
confidence: 55%
“…A dynamic and reversible Ca v α 1 -Ca v β association might play an important role in regulating Ca 2+ channel activity, especially during development when changes in the expression level of different Ca v β isoforms occur (311, 435, 449). It has been shown that the Ca v β component of N-type Ca 2+ channels changes during postnatal development, from β 1b > β 3 >> β 2 at P2 to β 3 > β 1b = β 4 at P14 and adult age (449).…”
Section: Stoichiometry and Reversibility Of The Cavα1-cavβ Intermentioning
confidence: 99%
See 1 more Smart Citation
“…Assembly of N-type VDCC subunits has been analyzed in several developing and differentiating systems (15). During IMR32 cell differentiation, ␤1b was up-regulated and increased in parallel with the expression of ␣ 1B (16).…”
mentioning
confidence: 99%
“…Interestingly, although Ca v 1.2 channels are targeted to the soma and dendrites of mature neurons, they are abundantly expressed in the growth cone of developing nerve cells [156]. It is conceivable that this switch in the expression pattern of Ca v 1.2 switch might reflect the existence of a dynamic and reversible association of the channel with different β isoforms [180,181]. Consistent with this notion, a reshuffling of the molecular composition of the N-type channel complex during postnatal development was documented, from β 1b > β 3 >> β 2 at P2 to β 3 > β 1b = β 4 at P14 and the adult stage [182].…”
Section: Mechanisms Of Subcellular Targeting Of Vgccsmentioning
confidence: 99%